Penilaian Pengelolaan Teknologi Informasi Dengan Menggunakan Kerangka Kerja COBIT Pada Domain Deliver & Support - Jolsvi Daely (LPPM Universitas Dhyana Pura, 2015)
Lack of state support of telecommunications facilities as a branch of the external resistance factor, making PT. Carrefour Indonesia often experience less than the maximum target achievement. Cope with this, companies adapt by strengthening internal factors in order to close the gap caused by external factors. However, the company is difficult to determine in detail the internal factors which need to be strengthened. To that end, research is done on the management of information technology to map all the activities, based on the framework COBIT (Control Objectives for Information and related Technology).The methods used in the research management of information technology, namely: (1) Method of Control Objectives (Control Objective, (2) Method of Analysis Causal KPI (Key Performance Indicator) and KGI (Key Goal Indicator ). The Maturity Model is a method that can be used to assess the scale of maturity in the process of managing an information technology. Based on the research conducted, PT. Carrefour Indonesia has already reached the 3.674; above the standard international average is 3,000. But when viewed from a predefined target management is at position 3.915, then the gap created by (0.241) compared to the conditions that exist today. The existence of advice on the issue, expected to be a meaningful input for PT. Carrefour Indonesia in continuous progress.Keywords: Management, COBIT, Control Objectives, Causal Analysis KPI and KGI, Maturity Model, gap